The impacts of the trade liberalization of environmental goods on power system and CO2 emissions. (May 2020) - Hu, Xiurong; Pollitt, Hector; Pirie, Jamie; Mercure, Jean-Francois; Liu, Junfeng; Meng, Jing; Tao, Shu
Abstract: The trade liberalization of Environmental Goods (EG), through as Environmental Goods Agreement (EGA), is crucial in low carbon electricity technology diffusion. However, there is a big gap of the EG definition lists and the integrated effectiveness analysis of EGA. This paper analyses the effects of the trade liberalization of EG based on macroeconomic and electricity sector models and attempts to find a more efficient EG trade policy by comparing different EG lists, considering end-use control and combining the EG policy with a carbon tax. The results show that the trade liberalization of EG does not necessarily benefit the environment without other policies, as the effects of the multiple end-uses of EG on conventional energy might result in environmental damage. We find that merging an EGA into a global carbon tax system would enhance the effects of carbon tax on CO2 reduction by 33%, and simultaneously lower the GDP loss due to the carbon tax by 75%. The economic benefits from the EGA could offset the costs of other environmental policies. Thus, end-use control and other environmental policies should be considered at both the global and regional levels in the setting of international trade agreements that target EG. Highlights: Free trade agreement of Environmental Goods (EGA) has trivial benefits to environment. Merging EGA into a carbon tax system would enhance CO2 reduction with GDP loss. End-use control should be considered at both global and regional levels in EGA.